2013
DOI: 10.3844/ajabssp.2013.82.88
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of In Vitro Antibacterial Activity of Miswak Extracts and Different Toothpastes

Abstract: This study determines the antimicrobial efficacy of miswak (aqueous and alcoholic) extracts comparing with five different toothpastes, which are available in Iraqi market, against different kinds of bacteria. The antibacterial efficacy of aqueous and alcoholic extracts of Salvadora persica and different kinds of toothpastes was studied against different cariogenic and pathogenic bacteria including Streptococcus mutans, Lactobacillus acidophilus, Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
2
18
1
1
Order By: Relevance
“…[19][20][21] Our results also showed that these mouthwashes can be used as an additional plaque control technique along with mechanical method of plaque control these results were in contrast to the results obtained by Loe et al 22 despite its antibacterial properties, chlorhexidine has certain limitations in its use includes both teeth and tongue stains on its long-term use. 16 This study also has certain limitations.…”
Section: Discussioncontrasting
confidence: 56%
“…[19][20][21] Our results also showed that these mouthwashes can be used as an additional plaque control technique along with mechanical method of plaque control these results were in contrast to the results obtained by Loe et al 22 despite its antibacterial properties, chlorhexidine has certain limitations in its use includes both teeth and tongue stains on its long-term use. 16 This study also has certain limitations.…”
Section: Discussioncontrasting
confidence: 56%
“…Phytochemical constituents such as alkaloids, flavonoids, tannins, phenolics, saponins, terpenoids and alternative aromatic compounds are secondary metabolites that are created in plants as a response to stress or as a part of their defense reaction against prediction by several microorganisms, insects and alternative herbivores [28]. Plants phenols and flavonoids are necessary teams of natural antioxidants and have a larger tendency to cure several sicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have reported the antibacterial and antifungal effects of miswak on cariogenic bacteria and periodontal pathogens including Staphylococcus aureus , Streptococcus mutans , Streptococcus faecalis , Streptococcus pyogenes , Lactobacillus acidophilus , Pseudomonas aeruginosa , Aggregatibacter actinomycetemcomitans , Porphyromonas gingivalis , Haemophilus influenzae , and Candida albicans [ 10 16 ]. Moreover, data from controlled clinical studies showed that Salvadora persica extract is also an effective antimicrobial agent when utilized clinically as an irrigant in the endodontic treatment of teeth with necrotic pulps [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%